Critical success factors and barriers for e-learning success in Saudi Arabian universities - Naveed, Quadri Noorulhasan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2019)
With the innovation and advancement of information and data communication technology, E-Learning has become an essential part of the teaching-learning environment. E-Learning has developed rapidly and implemented widely in the Arab world. The Kingdom of Saudi Arabia (KSA) is taking aggressive initiatives to embark on E-Learning, especially in order to integrate its wide spread population geographically; and to provide an equal opportunity for all genders and social strata. In spite of its fruitful execution, many E-Learning ventures hasn't accomplished its planned objectives and goals to the full extent. This has inspired many stakeholders, both from the industries and academia, to investigate the reasons behind the poor accomplishments of E-Learning, its Critical Success Factors (CSFs), and Barriers related to successful implementation. The present research reviewed the previous literature related to E-Learning and found 36 E-Learning CSFs and 16 Barriers for successful implementation of E-Learning. A structured research design was developed to incorporate all the established research procedures. By using a quantitative approach, this research tried to investigate the most important Critical Success Factors (CSFs) and Barriers related to successful implementation of E-Learning in Saudi Arabian Universities. A questionnaire-based survey was performed to identify the most important CSFs and Barriers, and to establish priority among CSFs and Barriers. Non-Probability and Convenience sampling were used to complete this study. The study was conducted to establish the exploratory, descriptive, and hypotheses which were tested and supported empirically. Analytic Hierarchy Process (AHP) involving Group Decision Making (GDM) methodology was employed to identify diversified dimensions and factors of E-Learning to determine the influence and rank of each factor in E-Learning. The population and sample for this study were taken from different universities of the Kingdom of Saudi Arabia. A total of 257 respondents have completed the questionnaire survey including teaching staffs, technical staffs, and students. The survey analysis revealed important CSFs and Barriers that influence the successful implementation of E-Learning in the Saudi Arabian Universities. The main contribution of this research includes the identification of 5 important CSFs such as Financial Readiness, Efficient Technology Infrastructure, Attitude towards E-Learning, Infrastructure Readiness, Commitment towards Online Studies and 4 most important Barriers such as Lack of Financial Support, Inappropriate Infrastructure, Lack of Training on E-Learning, Low Internet Bandwidth through intense review of literature and the quantification of each CSFs and Barriers using survey and AHP modelling. This quantification will help the policy-makers and different stakeholders as a future planning tool for successful E-Learning implementation in the universities. Some significant recommendations are suggested that will be helpful for the progress of E-Learning in the teaching-learning environment of Saudi Arabia.